Molecular detection and phylogeny of Ehrlichia canis and Anaplasma platys in naturally infected dogs in Central and Northeast Thailand - Andaman Purisarn; Sakulchit Wichianchot; Cherdsak Maneeruttanarungroj; Bandid Mangkit; Wuttinun Raksajit; Sarawan Kaewmongkol; Thitichai Jarudecha; Wanat Sricharern; Rucksak Rucksaken (My University, 2022)
Background and Aim: Ehrlichia canis and Anaplasma platys are tick-borne, Gram-negative bacteria that cause canine monocytic ehrlichiosis and canine cyclic thrombocytopenia, respectively. These diseases are of great importance and are distributed globally. This study aimed to create new primers for the identification of E. canis and A. platys in naturally infected dogs using polymerase chain reaction (PCR), DNA sequencing, and phylogenetic analysis using the 16S rDNA and gltA genes. Materials and Methods: In total, 120 blood samples were collected from dogs in three different locations (Saraburi, Buriram, and Nakhon Ratchasima provinces) in Central and Northeast Thailand. The molecular prevalence of E. canis and A. platys was assessed using PCR targeting the 16S rDNA and gltA genes. All positive PCR amplicons were sequenced, and phylogenetic trees were constructed based on the maximum likelihood method. Results: Ehrlichia canis had an overall molecular prevalence of 15.8% based on the 16S rDNA gene, compared to 8.3% based on the gltA gene. In addition, the overall molecular prevalence of A. platys using the 16S rDNA gene was 10.8%, while the prevalence rate was 5.8% using the gltA gene. Coinfection was 0.8% in Saraburi province. The partial sequences of the 16S rDNA and gltA genes of E. canis and A. platys in dogs in Central and Northeast Thailand showed 96.75%–100% identity to reference sequences in GenBank. Phylogenetic analysis of the 16S rDNA and gltA genes revealed that E. canis and A. platys sequences were clearly grouped into their own clades. Conclusion: This study demonstrated the molecular prevalence of E. canis and A. platys in Central and Northeast Thailand. The 16S rDNA and gltA genes were useful for the diagnosis of E. canis and A. platys. Based on the phylogenetic analysis, the partial sequences of the 16S rDNA and gltA genes in E. canis and A. platys were related to prior Thai strains and those from other countries.
Keywords: Ehrlichia canis; Amplicon; Vector-borne infectious diseases